2017
DOI: 10.1002/bdr2.1094
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, Expression of PAX3 and P53, and Caspase Signal in Fetuses with Neural Tube Defects

Abstract: These findings provide some evidence that excessive apoptosis in fetal central nervous tissues may be associated with the development of human NTDs. Birth Defects Research 109:1596-1604, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…Interestingly, our previous studies found higher levels of oxidative damage markers in the serum of pregnant women who delivered NTD-affected foetuses than women who delivered healthy newborns [28] . Furthermore, we observed more apoptotic cells in neural tissues of NTD cases than normal foetuses [25] . It is well documented that PAHs could induce oxidative stress and human observational studies suggest an association between PAH exposure and oxidative damage with increased risks of NTDs.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Interestingly, our previous studies found higher levels of oxidative damage markers in the serum of pregnant women who delivered NTD-affected foetuses than women who delivered healthy newborns [28] . Furthermore, we observed more apoptotic cells in neural tissues of NTD cases than normal foetuses [25] . It is well documented that PAHs could induce oxidative stress and human observational studies suggest an association between PAH exposure and oxidative damage with increased risks of NTDs.…”
Section: Introductionmentioning
confidence: 63%
“…Apoptosis occurs at various developmental stages as a homeostatic mechanism to maintain cell populations in tissues [24] . During the formation of the neural tube, apoptosis appears to be dispensable; however excessive apoptosis could potentially result in NTDs by causing insufficient cells to be present in the fusing neural folds or by disrupting the physical continuity of the dorsal midline [1] , [25] . Excess apoptosis is observed in the neuroepithelium of rodent embryos exposed to high levels of glucose in maternal serum, and deletion of pro-apoptosis kinase genes reduces the incidence of NTDs in these embryos [26] , [27] .…”
Section: Introductionmentioning
confidence: 99%
“…In human NTDs cases, more apoptotic cells were observed in the central nervous tissue [71]. Higher levels of p53 were observed in anencephaly cases [71]. Cleaved caspase 3 levels were elevated in encephalocele cases and cleaved caspase 8 levels were higher in spina bifida cases relative to controls [71].…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, excessive apoptosis in the lumbar sacral neuroepithelium has been observed with retinoic acid-induced spina bifida [70]. In human NTDs cases, more apoptotic cells were observed in the central nervous tissue [71]. Higher levels of p53 were observed in anencephaly cases [71].…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were recruited from five rural counties of Shanxi Province (Xiyang, Shouyang, Taigu, Pingding, and Zezhou) in northern China from 2011 to 2014 (Wang et al 2017). The NTD cases were fetuses terminated following the prenatal diagnosis of an NTD.…”
Section: Study Populationmentioning
confidence: 99%